Process of Adopting Information and Communication Technology (ICT) Innovations in Vocational Learning for Autism Spectrum Disorder (ASD) Students during the Covid-19 Pandemic - Firmansyah, Dwi; Lubis, Djuara P.; Muljono, Pudji; Purnaningsih, Ninuk (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Online learning demands specific teacher preparation, particularly in the effective utilization of Information and Communication Technology (ICT) innovations tailored to the unique needs and capabilities of students with autism spectrum disorder (ASD). This study focused on the ICT innovations adopted by educators at the London School Beyond Academy (LSBA), a vocational school catering to autistic students in Jakarta, during the COVID-19 pandemic. A total of 8 main informants who are educators were selected by snowbowling sampling. Data collection involved multiple methods, including in-depth interviews, observations, and literature reviews. Documentation included archiving interview recordings, interview transcripts, and observation notes. The data analysis technique was carried out by adopting the conceptual framework of "School Improvement" (Huberman & Miles, 1984). The findings revealed that the adoption of technological innovations at LSBA is a collaborative effort involving school administrators, educators, and academics, all of whom work together to tailor the use of ICT to the unique abilities of each ASD student. During the assessment of new students, psychologists and educators encountered challenges in conducting online observations. Consequently, this circumstance necessitated adjustments to the learning system to accommodate the diverse abilities of ASD students.